Surgical treatment and pneumatic reduction for intussusception in a pediatric patient with blue rubber bleb nevus syndrome - A.J. Cavazos Castro; E. Espinosa Guerrero; A. Pajaro Vallín; J. Asz Sigall (Elsevier, 2022)
Blue rubber bleb nevus syndrome is a congenital disorder characterized by the presence of venous malformations in the skin and gastrointestinal tract. On rare occasions, these venous malformations can cause intussusception. We present a case of a child known with Bean syndrome who arrived with intestinal occlusion requiring emergency laparotomy. Surgical findings included four intussusception zones through the jejunum and ileum, meriting ileum resection and primary anastomosis. During the next month he presented on two occasions with intussusception symptoms, requiring fluoroscopy-guided pneumatic reduction.